Modern aspects of diagnosing purulent pathology of the ear (Review of cases of middle ear cholesteatoma using non-EPI DWI MRI) - Asel Imangalieva (Journal of Otology, 2025)
Chronic suppurative otitis media (CSOM) is a prevalent condition in otolaryngology with significant medical and social implications, including hearing loss and severe intracranial complications. This article discusses the challenges in diagnosing cholesteatoma, a common complication of CSOM, particularly when using computed tomography (CT) and magnetic resonance imaging (MRI). We present three clinical cases where MRI, particularly in the non-EPI diffusion-weighted imaging (DWI) and apparent diffusion coefficient (ADC) modes, effectively identified the presence and extent of cholesteatoma that CT could not reliably distinguish due to overlapping features with other soft tissue formations. The high sensitivity of MRI, highlight its value in both primary diagnosis and assessment of recurrence. Our findings advocate for the incorporation of MRI into the diagnostic protocols for CSOM in the Republic of Kazakhstan, emphasizing the need for reliable epidemiological data to inform future research and prevent potential intracranial complications.